Research of the Island Folk Sports “Flea Dance” - Guoliang Zhang (Forest Chemicals Review, 2022)
Folk dance is an indispensable part of folk sports activities. In 1985, "Flea dance" was included in the National National Dance Collection, and in 2005, it was listed in the first batch of Intangible cultural Heritage protection list of Zhejiang Province. Its inheritor, He Zhifu, was positioned as the representative inheritor of Zhejiang Intangible cultural Heritage (Flea Dance). Flea dance is now one of the 20 endangered traditional folk arts to be saved and is applying for intangible cultural heritage protection from The State Council. "Flea dance", as a dance project of an island city, has the distinctive characteristics of folk sports dance. It can quickly catch the attention of the audiences as soon as its entrance and has become a wonderful curiosity among various folk sports dances. This is because flea dance presents a style totally different from the others, and owns uniquely social metaphor and cultural connotation. Investigating and exploring its modern evolution and cultural significance will facilitate to promoting the inheritance and development of this intangible cultural heritage project, and provide a reference for other folk sports dances. With comprehensive application of literature and interview, this paper reviews, analyzes, and interprets the flea dance thoroughly. Among the unique characteristics of flea dance, "Carnival Dance" displays the happiness and open-mindedness of fishermen. "Drama Action" implies the social imagine of fishermen seeking protection. "Men disguised as women" coincides with the traditional gender concept. "Funny absurdity" interprets the deliberate avoidance from rationality. "Flirting and teasing" restores the original lust of human nature. "Audience interaction" represents the construction and identification of social relations. "Flea dance" is a complex of religious symbols, artistic performances and folk sports with the unique style of island fishermen. Its modern evolution is embodied in three dimensions of mythic "meaning" in connotation, integration and symbiosis in structure, and pluralistic reconstruction in style. "Flea dance" is a complex of religious symbols, artistic performances and folk sports. In the process of inheritance and development, it has undergone a series of modern changes and made great efforts for the vigorous extension of its vitality.